White-emitting carbon dots with long alkyl-chain structure: Effective inhibition of aggregation caused quenching effect for label-free imaging of latent fingerprint. (March 2018) - Jiang, Bang-Ping; Yu, Yun-Xiang; Guo, Xiao-Lu; Ding, Zhao-Yang; Zhou, Bo; Liang, Hong; Shen, Xing-Can
Abstract: The surface functionalization of carbon dots (CDs) can introduce an additional dimension for the control of their photoluminescence properties and effective promotion of the applications of CDs such as imaging, sensing, etc . In this study, a simple one-step carbonization using Tween 80 as the sole carbon source is described for directly synthesizing white-emitting CDs (WCDs) in high yield. The results revealed the presence of several long alkyl chains on the surface of the as-fabricated WCDs, which effectively suppress the aggregation-caused quenching (ACQ) effect and emit bright white luminescence under an UV illumination of 365 nm in the solution and solid states. Besides, together with the surface protection of long alkyl chains, WCDs preferentially interact with lipophilic fatty residues and are beneficial for the label-free imaging of latent fingerprints. This study provides a promising new method to not only effectively inhibit the intrinsic ACQ effect of CDs but also develop the surface engineering of functionalized white-emitting CDs for practical applications via facile synthesis. Graphical abstract: Image 1